A Smart Sensing Cannula for Fat Grafting. Issue 2 (August 2019) - Turer, David M.; Qaium, Ehsan B.; Lawrence, April M.; Clark, William W.; Rubin, J. Peter
Abstract : Summary: Gluteal fat grafting has been highlighted as a significant safety issue in plastic surgery, with a mortality rate as high as one in 3000 cases. Injury to the gluteal veins resulting in fat emboli has been identified as the cause of these mortalities. The gluteal veins lie deep to the gluteal musculature in the buttocks, and it has been suggested that avoiding intramuscular injection of fat may prevent these complications. The authors present a novel injection cannula design that uses impedance sensing to determine the location of the cannula tip. Specifically, the system can determine when the tip of the cannula leaves the subcutaneous plane and enters muscle. The use of this system may prevent inadvertent injury to the gluteal veins and subsequent embolic complications. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V. Abstract : Supplemental Digital Content is available in the text.